Parental Attunement, Insightfulness, and Acceptance of Child Diagnosis in Parents of Children With Autism: Clinical Implications - Di Renzo, Magda; Guerriero, Viviana; Zavattini, Giulio Cesare; Petrillo, Massimiliano; Racinaro, Lidia; Bianchi di Castelbianco, Federico (Frontiers in Psychology, 2020)
Early parent-child relationships are an important factor influencing many domains of child development, even in the presence of autism. In this study, we investigated the associations between parent-child attunement during play, parental insightfulness, and parental acceptance of their child’s diagnosis of an autism spectrum disorder. A sample of 50 parents (26 mothers and 24 fathers) of 26 children aged between 24 and 58 months were videotaped during parent-child play interactions and then interviewed about what they thought had gone through their child’s head during the play interaction, and about their feelings and thoughts about their child’s diagnosis. Play interactions were evaluated using a coding protocol to assess parental attunement. The results showed that parents who who were more able to accept their child’s diagnosis and to see things from their child’s perspective were more likely to also be attuned during play interactions with their children. These findings highlight the importance of studying the parental ability of insightfulness and acceptance of their child diagnosis of ASD for the implementation of intervention programs for supporting parental attunement and improving the interactions between the parents and the children with autism spectrum disorders.